Pharmacoeconomic evaluation of direct oral anticoagulants for cancer-associated thrombosis: a systematic review - You, Xiaoyan; Liu, Yang; Wang, Xianying; Qin, Jiali; Wang, Xiaomei (Frontiers in Public Health, 2025)
ObjectiveTo synthesize pharmacoeconomic evidence of prevention and treatment of venous thromboembolism (VTE) in cancer patients with direct oral anticoagulants (DOACs) and evaluate the quality of the studies.MethodsPubMed, Embase, Scopus, the Cochrane Library, the Center for Reviews and Dissemination Database, the Health Technology Assessment Database, and the China National Knowledge Infrastructure Database were searched to collect economic evaluations. The search covered publications from their inception until June 13, 2024. Study selection was conducted independently by two researchers, with discrepancies resolved through discussion. The quality of the studies were assessed using the Consolidated Health Economic Evaluation Reporting Standards 2022 checklist, and the basic characteristics of the included studies were summarized descriptively.ResultsA total of 15 studies were included, covering different income level countries: the United States, Spain, China, the Netherlands, Canada, and Brazil. Economic evaluation results for prevention strategies varied in different countries. The baseline VTE incidence and drug costs will determine whether DOACs are worthwhile. For the treatment of VTE in cancer patients, DOACs were found to be more cost-effective compared to low molecular weight heparins (LMWHs) and warfarin, though the incremental cost-effectiveness ratio varied significantly across countries. However, there is still a lack of pharmacoeconomic studies based on direct evidence on which DOAC to choose for VTE treatment in cancer patients.ConclusionThe cost-effectiveness of DOACs for VTE in cancer patients has been proven. Further research is needed to determine the best choice of DOAC. Thromboprophylaxis in all cancer patients is not recommended. It is still necessary for clinicians to evaluate the risk of VTE. Pharmacoeconomic study results are significantly influenced by the drug costs, patient preferences, and income levels of different countries and regions. Economic decisions should be made according to the specific national background.